1989
DOI: 10.1002/1097-0142(19890601)63:11<2348::aid-cncr2820631146>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The United States experience with oral controlled-release morphine (MS contin tablets).parts i and ii. review of nine dose titration studies and clinical pharmacology of 15-mg, 30-mg, 60-mg, and 100-mg tablet strengths in normal subjects

Abstract: The results of nine US multicenter, sequential crossover, dose titration studies of controlled-release oral morphine (MS Contin 30 mg tablets [MSC], Purdue Frederick, Norwalk, CT) are reviewed in Part I. The studies demonstrated the prolonged analgesic efficacy of the preparation in the treatment of patients with moderate to severe cancer-related pain. Approximately 93% of the patients achieved satisfactory to excellent analgesia on a 12-hour regimen when appropriate dose titration was allowed. The remaining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…15,16 Only one paper confirmed having patients with hepatic impairment; 17 the subjects were five alcoholic cirrhotics. One report containing details of three studies 18 stated that the number of subjects in each study was between 20 and 24; for the purposes of our analysis, each study was assumed to have 20 subjects. One report 19 was a followup of an included study 10 and therefore contained duplicated data; only the new data was used from the later report.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Only one paper confirmed having patients with hepatic impairment; 17 the subjects were five alcoholic cirrhotics. One report containing details of three studies 18 stated that the number of subjects in each study was between 20 and 24; for the purposes of our analysis, each study was assumed to have 20 subjects. One report 19 was a followup of an included study 10 and therefore contained duplicated data; only the new data was used from the later report.…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to other opioid dose titration studies examining the pharmacokinetics of orally administered opioids. 4,5 In a study review done by Kaiko et al, it was shown that two 15-mg controlled-release oral morphine tablets were the same as one 30-mg tablet, two 30-mg tablets equaled one 60-mg tablet, and three 30mg tablets equaled one 100-mg tablet with respect to pharmacokinetic parameters. 5 The mean plasma morphine versus time curves for these three study comparison groups were very similar.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In a study review done by Kaiko et al, it was shown that two 15-mg controlled-release oral morphine tablets were the same as one 30-mg tablet, two 30-mg tablets equaled one 60-mg tablet, and three 30mg tablets equaled one 100-mg tablet with respect to pharmacokinetic parameters. 5 The mean plasma morphine versus time curves for these three study comparison groups were very similar. The differences in AUC, Tmax, and Cmax for these different dosage groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose administration of opioids can cause rash and itching. Growing evidence shows that the stimulation caused by the direct degranulation and activation of mast cells and the activation of opioid receptors lead to the release of histamine, causing skin reactions such as flushing, rash, urticaria, and itching (10)(11)(12).…”
Section: B Amentioning
confidence: 99%